In vitro screening for salt stress tolerance of native and exotic potato genotypes by morphological and physiological parameters (Journal of Bio-Science, 2019)
This study was performed on in vitro bioassay screening for salt tolerance of ten native and six exotic potato genotypes in Bangladesh. Single node was used to evaluate salinity tolerance especially on biomass production. Five different concentrations of NaCl (0 = control, 100, 150, 200 and 250 mM) were used in addition to MS medium and evaluated salt tolerant and sensitive genotype by various morphological and physiological parameters e.g. shoot and root length and its thickness, number of leaves and roots, fresh and dry weight of whole plant and water contents. The ANOVA, DMRT and correlation coefficient were found highly significant at p